Radius= 7cm
Base area= 49pi
Volume= 49pi*4= 196pi=615.75cm^3
Step-by-step explanation:
multiplying expressions.
remember every term of one expression has to be multiplied with every term of the other expression, and the results are added up (while considering their individual signs, of course).
1.
(-3×3 + 2x - 4)(3x - 2)
(-9 + 2x - 4)(3x - 2)
(-13 + 2x)(3x - 2) = -13×3x + -13×-2 + 2x×3x + 2x×-2 =
= -39x + 26 + 6x² - 4x = 6x² - 43x + 26
2.
let's do the other multiplication and compare the result with the result of 1 :
(-13 + 2x)(2x - 3) = -13×2x + -13×-3 + 2x×2x + 2x×-3 =
= -26x + 39 + 4x² - 6x = 4x² - 32x + 39
no, this product is not the same as in 1.
What do you need help in?
This =2.4 I hope that this helps you